Prior corticosteroid treatment alters cPBMC composition and IFNγ response to immunotherapy in canine cancer - Zimmermann, Anna Barbara Emilia; Taskoparan, Betül; Fuchs, Daniel; Pantelyushin, Stanislav; Maheswaran, Mathischan; Schnyder, Manuela; Hartnack, Sonja; Rohrer Bley, Carla; vom Berg, Johannes (Frontiers in Immunology, 2025)
BackgroundImmunotherapy using immune checkpoint inhibitors (ICIs) represents a promising therapeutic approach for canine cancer patients. Similar to human cancer patients, the concurrent use of corticosteroids may attenuate the efficacy of immune checkpoint inhibitors in dogs. In this study, we evaluated the impact of corticosteroid therapy on canine peripheral blood mononuclear cell (cPBMC) composition and the in vitro response to Programmed Death-1/Programmed Death-Ligand 1 (PD-1/PD-L1) axis blockade and recombinant human Interleukin-12 (rhIL-12) stimulation. MethodscPBMC samples were collected from 24 healthy, 44 cancer-bearing untreated, and 33 cancer-bearing corticosteroid pre-treated dogs. Lymphocytes were polyclonally stimulated with Staphylococcal Enterotoxin B (SEB) and either atezolizumab, a cross-functional anti-PD-L1 ICI, or rhIL-12. We analyzed the absolute and relative changes in canine interferon-gamma (cIFNɣ) production. Stimulation with gilvetmab, a recently developed canine anti-PD-1 ICI, revealed comparable results to atezolizumab. Moreover, we assessed the influence of corticosteroid pre-treatment on cPBMC composition by flow cytometry. ResultsCorticosteroid treatment significantly affected the immune profile, primarily the monocytic compartment, and functional cIFNɣ response of cPBMCs. Nevertheless, responses to immunotherapy appeared to be highly individual. ConclusionsOverall, we observed trends suggesting that prior corticosteroid therapy may compromise the efficacy of PD-1/PD-L1 axis blockade and IL-12 in dogs with cancer. While the dose and timing of corticosteroid administration in this study reflected clinical reality and would not justify withholding this emerging therapeutic option, corticosteroid pretreatment may be a confounder for PD-1/PD-L1 axis blockade or IL-12 therapy in canine oncology.